Development of flat gain and wide-band erbium doped fiber amplifier using hybrid active medium / Aya Ali Hasan Almukhtar - Aya Ali , Hasan Almukhtar (2019)
Efficient L-band amplifiers were successfully achieved using two types of new Erbium-doped fiber; Zr-EDF and HB-EDF as a gain medium. Both fibers have a significantly high Erbium ions concentration. For instance, the enhanced Zr-EDF has an erbium ion concentration of 4000 ppm while the HB-EDF has ion concentration of 12500 ppm. For enhance Zr-EDF, a significant flat gain of about 17.1 dB was achieved with gain variance of less than 1 dB within band over 40 nm wavelength region for double-pass setup at input power of -10 dBm. The noise figure for double-pass was provided higher spectrum as compared with single-pass. For new HB-EDF, an efficient flat gain of about 15 dB was achieved at gain variance of around 1 dB over wavelength area from 1560 to 1605 nm in double-pass configuration. The performance of HB-EDFA was compared with enhance Zr-EDFA performance in double-pass configuration. The Zr-EDFA has relatively higher gain as compared to that of HB-EDFA over wavelength region from 1565 to 1610 nm at input signal power of -10 dBm. However, a shorter length of 1.5 m was used for the HB-EDF amplifier which is half of the Zr-EDF length as well as the new HB-EDFA provided wider bandwidth amplification started from 1545 nm. The corresponding noise figure of the proposed HB-EDFA was lower as compared to that of Zr-EDFA. An efficient hybrid amplifier with wideband and flat gain characteristics was demonstrated using a combination of Bi-EDF and HB-EDF with total optimal length of 1.99 m in double-pass parallel configuration. This amplifier provided flat gain of 14 dB with gain fluctuation less than 1.5 dB over 75 nm wavelengths at high input power of -10 dBm. An efficient wideband EDFA operating in wideband wavelength region was also obtained using two pieces of Zr-EDFs as gain media for both stages, with total length of 3.5 m in double-pass parallel configuration. The proposed amplifier also provided a wideband and high flat gain of 17.1 dB with gain fluctuation less than 1.5 dB within wavelength region from 1525 to 1600 nm at input signal power of -10 dBm. A wideband flat gain amplification was investigated using partial double-pass which is using both HB-EDF and Zr-EDF as the gain mediums. At input signal of -10 dBm, a flat gain of around 17.2 dB is obtained with a gain fluctuation of less than 2.3 dB within the 55 nm wavelength region from 1540 to 1595 nm. A novel dual-stage with triple-pass hybrid amplifier is investigated by comprise 2 stages of EDFA using both HB-EDF and Bi-EDF, as the gain medium. At high input power of -10 dBm, a flat gain of about 18.5 dB with gain variation less than 2 dB is observed across 45 nm bandwidth. The noise figure varied from 4.8 to 9.3 dB within the flat gain region. The triple-pass EDFA has been enhanced by utilizing distribution pumping scheme to minimize the cost of the amplifier yet having the comparable performance with the dual-pump configuration.